MUDANÇAS E DIFERENÇAS EPIGENÉTICAS NA ORGANOGÊNESE E EMBRIOGÊNSE SOMÁTICA EM PASSIFLORA: INFLUÊNCIA DO EXPLANTE E DAS CONDIÇÕES IN VITRO - Leite, Cristiana Torres (2021)
The development of in vitro plants can be influenced by several factors, among them the explant source, the cultivation conditions and the global methylation of the genomic DNA. It is known that in species of Passiflora L. genus, different morphogenic responses are observed under the same conditions in vitro. Therefore, other factors may influence the response, such as the genetic, physiological and epigenetic aspects of the explant. We aim here to establish the in vitro morphogenesis process for three species of the genus Passiflora in order to verify and compare the influence of explant types, cultivation conditions and the global level of 5-methylcytosine. Our results showed that in Passiflora miniata the regeneration was through indirect somatic embryogenesis pathway, with the highest number of somatic embryos formed from immature zygotic embryos, in the absence of growth regulators and activated charcoal. Furthermore, the overall level of 5-methylcytosine decreased in the regeneration stage. In Passiflora cristalina and Passiflora foetida, the morphogenic pathway was indirect organogenesis, with the highest bud formation triggered by the use of mature zygotic embryos, the presence of growth regulators and activated charcoal, as well as the increase in the global level of 5-methylcytosine in the regeneration stage. From these different responses, we evidenced the influence of the developmental stage of the zygotic embryo, the use of growth regulators and activated charcoal and, for the first time, the global level of 5-methylcytosine during the in vitro development of Passiflora species.